Simulation and optimization of rice husk gasification using intrinsic reaction rate based CFD model. (August 2019) - Gao, Xiaoyan; Xu, Fei; Bao, Fubing; Tu, Chengxu; Zhang, Yaning; Wang, Yingying; Yang, Yang; Li, Bingxi
Abstract: Entrained flow gasification processes of rice husk were simulated and optimized in this study using an intrinsic reaction rate based CFD model. A detailed sensitivity analysis was conducted to characterize the effects of operation parameters on the gas composition, gas production and cold gas efficiency. Gasification temperature, average particle diameter, ER (equivalence ratio) and CO2 /biomass (mass ratio of carbon dioxide to biomass) are important operation parameters affecting the gasification process, and they were investigated in this study. Three-objective optimization of rice husk gasification was performed base on the response surface methodology (RSM) to maximize CO content, gas production, and cold gas efficiency, and the Pareto optimal solutions were obtained from NSGA-II (non-dominated sorting genetic algorithm) to instruct gasification operation. With standard TOPSIS (technique for order preference by similarity to ideal situation), the optimal solutions with CO concentration of 25.15%, gas production of 1.96 Nm 3 /kg and cold gas efficiency of 65.34% were obtained. Highlights: Entrained flow gasification processes of rice husk were simulated and optimized. Sensitivity analysis and multi-objective optimization were conducted. Effects of Gasification temperature, average particle diameter, ER and CO2 /bio were studied. Optimal CO concentration, gas production and cold gas efficiency were obtained.